Marching at the front and dragging behind: differential αVβ3-integrin turnover regulates focal adhesion behavior - Ballestrem, Christoph (The Rockefeller University Press, 2001)
Integrins are cell–substrate adhesion molecules that provide the essential link between the actin cytoskeleton and the extracellular matrix during cell migration. We have analyzed αVβ3-integrin dynamics in migrating cells using a green fluorescent protein–tagged β3-integrin chain. At the cell front, adhesion sites containing αVβ3-integrin remain stationary, whereas at the rear of the cell they slide inward. The integrin fluorescence intensity within these different focal adhesions, and hence the relative integrin density, is directly related to their mobility. Integrin density is as much as threefold higher in sliding compared with stationary focal adhesions. High intracellular tension under the control of RhoA induced the formation of high-density contacts. Low-density adhesion sites were induced by Rac1 and low intracellular tension. Photobleaching experiments demonstrated a slow turnover of β3-integrins in low-density contacts, which may account for their stationary nature. In contrast, the fast β3-integrin turnover observed in high-density contacts suggests that their apparent sliding may be caused by a polarized renewal of focal contacts. Therefore, differential acto-myosin–dependent integrin turnover and focal adhesion densities may explain the mechanical and behavioral differences between cell adhesion sites formed at the front, and those that move in the retracting rear of migrating cells.